Curricular Offerings in Small and Large High Schools: How Broad is the Disparity - Bruce Barker (Journal of Research in Rural Education, 1985)
Larger high schools can and do offer greater variety in their curricular offerings than do their small school counterparts. The purpose of this study was to measure the extent of that disparity. A survey of 105 different course offerings revealed that 36 percent were provided at significantly higher frequencies in large high schools whereas only two percent were offered at significantly higher frequencies in small schools. Significant differences were noted in all of the foreign language and advanced placement courses surveyed, and in almost one-half of art, business, mathematics, and social studies courses. School administrators should investigate alternative delivery systems and innovative practices which will expand program breadth in small high schools